a AKTIVITAS FAGOSITOSIS MAKROFAG MENCIT (Mus musculus L.) YANG DIINDUKSI EKSTRAK DAUN JERUK PURUT (Citrus hystrix D.C.) - Yeni avidhatul husnah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2019)
Kaffir lime (Citrus hystrix) is Indonesia native plant. During this time, the use of kaffir lime plants is still limited to a small portion spices ingredients and aromatherapy oils for industry. The compounds of leaves of C. hystrix are alkaloids, flavonoids, terpenoids, saponins, polyphenols, tannins, and essential oils that are cytotoxic to cancer cell lines. The purpose of this research was to determine the effect of cytotoxicity and phagocytosis activity induced by leaves extract of C. hystrix on macrophage cells and the potention leaves extract of C. hystrix as imunomodulator. This study include sampling kaffir lime leaves, extraction with ethanol and methanol, qualitative phytochemical analysis using Thin Layer Chromatography (TLC), test of cytotoxicity with WST-1 assay, and macrophage cell phagocytosis activity test. TLC test results of methanol and ethanol extract showed that the leaves of C. hystrix contain secundary metabolite these are: tannins, terpenes, saponins and flavonoids. Cytotoxicity test results showed that IC50 value of the methanol extract of kaffir lime leaves was 0.677 µg / mL and toxic to the macrophage cells. The phagocytosis assay showed that the index value, activity and phagocytic capacity of C. hystrix at various dose was lower compared to that of control cells. Methanol extract lime leaves did not to improve the index, activity and phagocytic capacity of macrophages. Methanol extract lime leaves did not potential as imunomodulator. Keywords: Citrus hystrix D. C, macrophages, cytotoxicity, WST-1 assay, phagocytic activity